Is genome size of Lepidoptera linked to host plant range?. Issue 3 (8th June 2016) - Calatayud, P.‐A.; Petit, C.; Burlet, N.; Dupas, S.; Glaser, N.; Capdevielle‐Dulac, C.; Le Ru, B.; Jacquin‐Joly, E.; Kaiser‐Arnauld, L.; Harry, M.; Vieira, C.
Abstract: Genome size varies considerably among organisms, largely as the result of differences in the content of non‐coding and/or repetitive DNA, such as introns, pseudogenes, or transposable elements, as well as whole‐genome duplications. Genome size is known to correlate with metabolic rates. Because polyphagy also affects the metabolism, a correlation between diet specialization and genome size can be expected. To test this hypothesis, a study was undertaken with five closely related species of stem borers which are easy to rear under artificial conditions, namely Busseola fusca (Fuller), Busseola segeta (Bowden), Busseola nairobica Le Ru, Sesamia calamistis Hampson, and Sesamia nonagrioides Lefebvre (all Lepidoptera: Noctuidae). However, as the number of species was too low for correlating diet with genome size in Lepidoptera in general, literature data from 16 Lepidoptera species were used in addition. The results pointed to a relationship between genome size and the insect's host plant range in Lepidoptera, but below the family level only, with larger genomes in polyphagous compared to specialist species. In addition, the genome size appeared to be influenced not only by host plant range but also by environmental/climatic conditions. Studies to test this hypothesis should be done strictly below the family level.